SEX-SPECIFIC GERIATRIC CHARACTERISTICS AMONG OLDER INPATIENTS AT AN BINH HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate sex-specific geriatric characteristics among older inpatients at An Binh Hospital.Methods: A cross-sectional study was conducted among patients aged ≥ 60 years admitted to seven clinical departments—Cardiology, Infectious Diseases, Endocrinology–Nephrology, Neurology, Geriatrics, Respiratory Medicine, and Gastroenterology—from October to December 2025.Results: A total of 257 older inpatients were enrolled, of whom women accounted for 63.4%. Compared with men, women had significantly lower educational attainment, greater financial dependency, and a higher mean BMI. Men had higher rates of alcohol consumption and tobacco use. Regarding geriatric characteristics, women exhibited significantly higher frailty based on the EFS, greater dependency in ADL and IADL, and a higher risk of cognitive impairment. For comorbidities, diabetes mellitus and knee osteoarthritis were more prevalent among women, whereas men showed a significantly higher prevalence of COPD.Conclusion: Sex was strongly associated with variations in frailty, functional dependence, cognitive impairment, and specific comorbidities among older inpatients.
Keywords: geriatrics, sex differences, older adults, older inpatients, An Binh Hospital.